2020
DOI: 10.3389/fmicb.2020.593088
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Whole-Plant Corn Silage With Lactic Acid Bacteria and Organic Acid Enhances Quality by Elevating Acid Content, Reducing pH, and Inhibiting Undesirable Microorganisms

Abstract: We investigated the variation in microbial community and fermentation characteristics of whole-plant corn silage after treatment with lactic acid bacteria (LAB) and organic acids. The fresh corn forages were treated with a combination of L. acidophilus and L. plantarum (106 CFU/g fresh material) or a 7:1:2 ratio of formic acid, acetic acid, and propionic acid (6 mL/g fresh material) followed by 45 or 90 days of ensiling. Silages treated with LAB showed increased lactic acid content and decreased pH after 45 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 51 publications
6
30
1
Order By: Relevance
“…Guan et al [2] and Gharechahi et al [12] also reported the unique bacterial community in whole-plant corn from different sampling sites. The abundance of Lactobacillus was 1.02%, 1.08% and 1.51% in H0, I0 and S0, respectively (Figure 3 and Supplementary Figure S1); the same results were reported by previous studies [2,[11][12][13][14][15]24,26]. This generally indicated that Lactobacillus is a minor taxon in whole-plant corn before ensiling.…”
Section: Discussionsupporting
confidence: 88%
“…Guan et al [2] and Gharechahi et al [12] also reported the unique bacterial community in whole-plant corn from different sampling sites. The abundance of Lactobacillus was 1.02%, 1.08% and 1.51% in H0, I0 and S0, respectively (Figure 3 and Supplementary Figure S1); the same results were reported by previous studies [2,[11][12][13][14][15]24,26]. This generally indicated that Lactobacillus is a minor taxon in whole-plant corn before ensiling.…”
Section: Discussionsupporting
confidence: 88%
“…This finding agrees the results of Kara [23] who observed that malic acid did not affect the composition of corn silage except decreased NDF contents. Similarly, Jiang et al [17] reported that whole plant corn ensiled with organic acid mixture (acetic acid, propionic acid, and formic acid at a 1:2:7 ratio) applied at 6 mL/g fresh material reduced NDF content in the silage. The decreased fiber content in organic acid-treated silages may be due to hydrolysis of digestible cell wall fractions by the action of organic acids during ensiling process [17,24].…”
Section: Chemical Compositionmentioning
confidence: 90%
“…Therefore, effective treatments of low-quality forages and materials can be used as a method of improving their nutritive value and chemical composition. Jiang et al [17] ensiled whole corn plant with organic acids and observed reduced NDF content in the silage. We hypothesized that malic acid or lactic acid treatment of DPL and RS during ensiling will raise the acidity rapidly, decrease the aerobic phase of fermentation, and accelerate the initiation of lag and anaerobic phases of silage, which may enhance the nutritional value of DPL and RS silage.…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation is a complex and dynamic process influenced by several factors including anaerobic conditions of the silo, quantity of water-soluble carbohydrates, abundance of epiphytic bacteria, dry matter quantity and buffering capacity of plant material (Weinberg and Muck, 1996). Different methods have been developed for efficient preservation of silage quality with the use of dry matters (Jiang et al 2020). High lactic acid content of graminae silages results in reduced silage pH, acetic, butyric and propionic acid contents and consequent formation of undesired harmful microbes for fermentation (Mohd-Setapar et al 2012;Salvucci et al 2016).…”
Section: Introductionmentioning
confidence: 99%